HERMENEUTIKA BHABINKAMTIBMAS PERSPEKTIF IMPLEMENTASI PEMOLISIAN MASYARAKAT BERBASIS KEMANDIRIAN DESA DALAM MEWUJUDKAN KEAMANAN DAN KETERTIBAN DI WILAYAH DESA TANGKIL KECAMATAN SRAGEN KABUPATEN SRAGEN - SUMARJI, SUMARJI (Dinamika Hukum, 2018)
The purpose of this research is to find out what the basics of Bhabinkamtibmas consider to build community policing based on village independence to realize security and order in the Tangkil Village of Sragen Subdistrict Sragen, as well as the obstacles that Bhabinkamtibmas have in building community policing to realize security and order in Tangkil Village in Sragen Subdistrict Sragen Regency. The background of the research is that the research was conducted in Tangkil Village in Sragen Subdistrict Sragen Regency. The research method consists of hermenetic research approach that is the data collection technique used by the method of field research through interview and literature study research, then from all the collected data done by qualitative analysis. Research findings show that Bhabinkamtibmas's role in building community policing is through working professionally by implementing community development, early detection and mediation / negotiation aimed at creating conducive conditions in rural areas. The obstacles experienced by Bhabinkamtibmas in maintaining and implementing security and order in the Tangkil Village area Sragen Subdistrict Sragen Regency: Internal Barriers: Binmas Unit / Bhabinkamtibmas Unit as the mainstay of the main government is still a duplicate of the work, Limitation of the ability of Bhabikamtibmas especially in the provision of construction material as well as communication techniques with the community, There is still a Bhabinkamtibmas assignment that is more than one hosted village. The absence of a continuous socialization of the other functions of the Police (Intel, reserse, traffic, sabhara) and Binmas's function regarding Bhabinkamtibmas and the empowerment of the Police. External Obstacles: Covering the presence of an Independent Police and Community Partnership Offices (BKPM) in both villages and subdistricts, the main activity of the policymakers of Bhabinkamtibmas to establish partnerships with the community has not been properly facilitated. The Polri and Community Partnership Forum (FKPM) in villages / villages as a vehicle for communication between the National Police and the community concerned with issues of social and social issues and seeking solutions on the basis of a collective agreement is less effective, this is due to the role Police in relation to Bhabinkamtibmas Officers do not play the maximum role because of the complexity and duplication of work. How to overcome the problem of Obtimalization of Bhabinkamtibmas in the construction area can be done through Human Resource Improvement through education, provision of Police and Community Partnership Center (BKPM), Placement of one village / village Bhabinkamtibmas personnel, Placement of Bhabinkamtibmas officers domiciled in their respective residential areas and professionalism with not duplicate work. Key words : Bhabinkamtibmas, community policing